Assessment of air pollution by toxic elements on petrol stations using moss and lichen bag technique - DEMKOVÁ, Lenka; BARANOVÁ, Beáta; OBOŇA, Jozef; ÁRVAY, Július; LOŠÁK, Tomáš (Plant, soil and environment, 2017)
Three moss (Pleurosium spp., Polytrichum spp., Rhytidiadelphus spp.) and two lichen taxa (Hypogymnia physodes L., Pseudevernia furfuracea L.), were exposed for four weeks in six petrol stations, two consecutive years (2015–2016), in urban area of the Prešov city (Slovakia), to assess accumulation of selected airborne elements Cd, Co, Cu, Fe, Hg, Mn, Ni, Pb and Zn. Significantly highest (P < 0.01) ability to accumulate Zn, Ni, Co and Fe was found in Pleurosium spp.; Pseudevernia furfuracea was determined the best accumulator of Hg, whereas Rhytidiadelphus spp. was found as the least suitable for this purpose. No significant differences in heavy metal accumulation between moss and lichen taxonomic group were found. Samples of conifer (used as a moss/lichen bag holder) showed significantly lower content of heavy metals compared to mosses and lichens. Major content of heavy metals trapped in the air around petrol stations, did not originate from the petrol combustion, but predominantly from the car body, which is mechanically disrupted during fuelling.